Privacy in America: Interdisciplinary Perspectives - Aspray, William; Doty, Philip (Rowman & Littlefield Publishers, 2011)
In this collection of essays that represent original and interdisciplinary work, respected scholars address a number of privacy issues. These include how governmental and private sectors develop and deploy technologies that can pose serious compromises to the privacy of individuals and groups; how information and communication system designs pose threats to privacy; how we manage private concerns (child care, job leave, and identity) as public issues amenable to political action and shared awareness; and the fundamental asymmetry of power that exists between individuals and small groups on the one hand and large governmental and corporate entities on the other. Arranged in three sections—law and policy; information technology; and information studies, history, and sociology—Privacy in America: Interdisciplinary Perspectives will be useful to scholars, practitioners, and students in a variety of fields, including information science, library science, and information systems.